2014
DOI: 10.1111/jam.12440
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus gasseriK7 modulates the blood cell transcriptome of conventional mice infected withEscherichia coliO157:H7

Abstract: Aims: As the immune cells underlying the intestinal barrier sense luminal microbial signals, blood cell transcriptomics may identify subclinical changes triggered by gut bacteria that may otherwise not be detected. We have therefore investigated how Lactobacillus gasseri K7 and enterohemorrhagic Escherichia coli O157:H7 modulate the blood cell transcriptome of mice possessing an intact microbiota. Methods and Results:We have analysed the transcriptome of five groups of C57BL/6J mice: (i) control, (ii) inoculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 53 publications
(80 reference statements)
1
2
0
Order By: Relevance
“…It was shown previously that both probiotic strains (LGG and LK7) can survive passage through the intestinal tract of mice after oral administration of probiotics (Blümer et al, 2007;Sagaya et al, 2014). In our study, we confirmed the presence of viable LGG and LK7 strains (>1 × 10 3 cfu/g) by strain-specific PCR in all samples from d 3 PP and in one sample from d 8 PP (Table 1).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…It was shown previously that both probiotic strains (LGG and LK7) can survive passage through the intestinal tract of mice after oral administration of probiotics (Blümer et al, 2007;Sagaya et al, 2014). In our study, we confirmed the presence of viable LGG and LK7 strains (>1 × 10 3 cfu/g) by strain-specific PCR in all samples from d 3 PP and in one sample from d 8 PP (Table 1).…”
Section: Discussionsupporting
confidence: 93%
“…Several studies have shown that different LAB and potential probiotics can stimulate the immune system and translocate to MLN of healthy adult mice without causing systemic infection (Zhou et al, 2000;Maragkoudakis et al, 2009;Kandasamy et al, 2011). Most likely, the application of probiotics resulted in an increased activation of the immune system (Gorbach, 2000;Sagaya et al, 2014) and increased sampling of beneficial commensal bacteria from the intestinal lu- men. Moreover, in pregnancy and lactation there could be an increased frequency of translocation of bacteria to MLN and migration of bacterial cells to MG via the entero-mammary pathway (Perez et al, 2007).…”
Section: Discussionmentioning
confidence: 98%
“…Strains of L. gasseri species are frequently declared to be probiotics (1). L. gasseri K7 is an isolate from infant feces and has established probiotic properties in vitro and in vivo (24). The gassericins K7 A (GenBank accession no.…”
Section: Genome Announcementmentioning
confidence: 99%